ASSISTANCE FOR THE COMMUNITY OF SEMPU HAMLET, NGADIROJO VILLAGE, MAGELANG REGENCY IN BIOCONVERSION OF ORGANIC WASTE INTO ALTERNATIVE FEED FOR MAGELANG DUCKS - Puji Rahayu, Tri; Trisnowati, Eli; Bayuaji Pramono, Pradipta (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Livestock is one of the livelihoods that contribute to the economy of the Indonesian people, one of which is the Magelang Duck livestock group "Sumber Makmur". However, the problem of high feed prices in the market causes the current profits obtained by the farmer group to be inadequate. In addition, another problem that occurs in the Sempu hamlet environment is the absence of a waste processing site. Residents have to wait for a team of officers who clean the surrounding environment so that garbage often accumulates, which causes pollution to the environment. Therefore, the service team offers a solution by assisting in the cultivation of Black Soldier Fly (BSF) larvae through Organic Waste Bioconversion. The activity was carried out using a Community Development approach, with socialization, training, and practice on the bioconversion process of organic waste using Hermetia illucens larvae. The training and mentoring activities received positive responses from the activity participants. Massive training and mentoring efforts can be carried out to solve environmental and economic problems, especially for Magelang Duck breeders.